New possibility of retrospective EPR dosimetry - Vorona, I.; Ishchenko, S.; Okulov, S.; Petrenko, T.T. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Tooth enamel plates irradiated by different types of radiation were studied by electron paramagnetic resonance imaging with local gradient of magnetic field. The dependence of radiation defect distributions on an irradiation type was found. A new procedure of retrospective electron paramagnetic resonancedosimetry determining the irradiation type was proposed.